Odpowiedzi

Najlepsza Odpowiedź!
2009-11-30T17:20:36+01:00
(x-5)²=(x-√3)(x+√3)
x²-10x+25=x²-3
10x=25+3
10x=28
x=2,8


(x+1)²+(x-1)²=2(x-1)(x+1)
x²+2x+1+x²-2x+1=2(x²-1)
2x²+2=2x²-2
0=-4


(3x-4)²+(2x+1)²=(5x+2)(5x-2)
9x²-24x+16+4x²+4x+1=25x²-4
13x²-20x+17=25x²-4
13x²-20x-25x²=-4-17
-12x²-20x=-21

d). 1-4(x+2)²=(1-2x)(1+2x)
1-4(x²+4x+4)=1-4x²
1-4x²-16x-16=1-4x²
-16x=1+15
-16x=16
x=-1


e). (3-2x)²+(x+4)(x-3)=5(x-2)²+7
9-12x+4x²+(x²-3x+4x-12)=5(x²-4x+4)+7
9-12x+4x²+x²-3x+4x-12=5x²-20x+20+7
-3-11x+5x²=5x²-20x+27
-11x+20x=27+3
9x=30
x=3 i 1/3



f)2(x-0,2)²=x²+(x+0,1)
2(x²-0,4x+0,04)=x²+x+0,01
2x²-0,8x+0,08=x²+x+0,01
x²-1,8x=-0,07
choc moim zdaniem jest źle przykład jest źle napisany powinno chyba być 2(x-0,2)²=x²+(x+0,1)²
2009-11-30T17:30:02+01:00
A). (x-5)²=(x-√3)(x+√3)
X²-10X+25=X²-3
-10X=-3-25
-10X=-28
X=2,8
b). (x+1)²+(x-1)²=2(x-1)(x+1)
X²+2X+1+X²-2X+1=2(x²-1)
2x²+2=2x²-2
nie ma rozwiazań
c). (3x-4)²+(2x+1)²=(5x+2)(5x-2)
9x²-24x+16+4x²+4x+1=25x²-4
13x²-20x+17=25x²-4
-12x²-20x+21=0
12x²+20x-21=0

d). 1-4(x+2)²=(1-2x)(1+2x)
1-4(x²+4x+4)=1-4x²
1-4x²-16x-16=1-4x²
-16x=1-1+16
x=-1

e). (3-2x)²+(x+4)(x-3)=5(x-2)²+7
9-12x+4x²+x²-3x+4x-12=5(x²-4x+4)+7
5x²-11x-3=5x²-20x+20+7
-11x+20x=27+3
9x=30
x=30/9

f). 2(x-0,2)²=x²+(x+0,1)
2(x²-0,4x+0,04)=x²+x+0,01
2x²-0,8x+0,08=x²+x+0,01
x²-1,8x+0,07=0